Unusual metallic conductivity of high-Tc cuprates - Dzhumanov, S; Malikov, Sh. R.; Djumanov, Sh. S. (Eurasian Journal of Physics and Functional Materials, 2026)
The intrinsic mechanisms of the unusual metallic transports of three types of relevant charge carriers (large polarons, excited (dissociated) polaronic components of bosonic Cooper pairs and bosonic Cooper pairs themselves) along the CuO2 layers of high-Tc cuprates are identified and the new features of metallic conductivity in the CuO2 layers (i.e. ab -planes) of underdoped and optimally doped cuprates are explained. The in-plane conductivity of high-Tc cuprates is associated with the metallic transports of such charge carriers at their scatteringbylattice vibrations in thin CuO2 layers. The proposed charge transport theory in high-Tc cuprates allows to explain consistently the distinctive features of metallic conductivity and the puzzling experimental data on the temperature dependences of their in-plane resistivity rab . In underdoped and optimally doped cuprates the linear temperature dependence of rab (T) above the pseudogap formation temperature T . is associated with the scattering of polaronic carriers at acoustic and optical phonons, while the different (upward and downward) deviations from the linearity in rab (T) below T . are causedbythe pseudogap effect on the conductivity of the excited Fermi components of bosonic Cooper pairs andbythe dominating conductivity of bosonic Cooper pairs themselves in the normal state of these high-Tc materials.Recommended CitationDzhumanov, S.; Malikov, Sh. R.; and Djumanov, Sh. S. (2021) "Unusual metallic conductivity of high-Tc cuprates," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 3, Article 3.DOI: https://doi.org/10.32523/ejpfm.2021050303